2013
DOI: 10.1186/1471-2261-13-17
|View full text |Cite
|
Sign up to set email alerts
|

Association of the angiotensinogen gene polymorphism with atherosclerosis and its risk traits in the Saudi population

Abstract: BackgroundAngiotensinogen (AGT) constitutes a central component of the renin-angiotensin system that controls the systemic blood pressure and several other cardiovascular functions and may play an important role in atherosclerosis pathways. In this study, we employed TaqMan genotyping assays to evaluate the role of 8 AGT variants in primary hypertension (HTN), type 2 diabetes mellitus (T2DM), and obesity as a possible trigger of coronary artery disease (CAD) in a population of 4615 angiographed native Saudi in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
21
0
2
Order By: Relevance
“…As AGT-increasing ?11525 C/A (rs7079) A allele (Mopidevi et al 2013) is only present in combination with the major allele of the three eQTL, the effects on AGT secretion are apparently contradictory and rs7079 CC homozygotic genotype responding to miR-31 and miR-584 binding thus compensate the overproduction of AGT caused by promoter variant. This LD can also explain the findings of Al-Najai et al where the C allele (G in antiparallel strain) and CC genotype were associated with a higher risk of hypertension (Al-Najai et al 2013). …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As AGT-increasing ?11525 C/A (rs7079) A allele (Mopidevi et al 2013) is only present in combination with the major allele of the three eQTL, the effects on AGT secretion are apparently contradictory and rs7079 CC homozygotic genotype responding to miR-31 and miR-584 binding thus compensate the overproduction of AGT caused by promoter variant. This LD can also explain the findings of Al-Najai et al where the C allele (G in antiparallel strain) and CC genotype were associated with a higher risk of hypertension (Al-Najai et al 2013). …”
Section: Discussionmentioning
confidence: 60%
“…The only study so far evaluating the effect of miRNA binding site ?11525 C/A (rs7079) on BMI was performed by Al-Najai et al In accordance with our results, no association with BMI was found; however, the polymorphism was associated with hypertension and coronary artery disease. ?11525 C/A (rs7079) was also found to be in LD with other polymorphisms in the AGT gene (Al-Najai et al 2013). Other studies focused on other polymorphisms of the AGT gene that are in LD with rs7079 (International HapMap Consortium 2003), with similar results.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the angiotensinogen is a key Experimental and Molecular Pathology 99 (2015) 128-132 component of RAS, it is cleaved by renin to produce angiotensin I. AGT gene presents five important single nucleotide polymorphisms (SNPs), three in the promoter region [− 6 ANG (rs5051), − 217 GNA (rs5049) and − 532 CNT (rs5046)] and two in the exon 2 [C4072T (rs699) and C3889T (rs4762)]. These SNPs have been associated with risk of developing hypertension, acute myocardial infarction, vascular disease, coronary artery disease, atherosclerosis, and coronary artery bypass graft in several populations (Inoue et al, 1997;Karayannis et al, 2010;Ragia et al, 2010;Mehri et al, 2011;Dzielinska et al, 2011;Abd El-Aziz et al, 2012;Al-Najai et al, 2013;Brugts et al, 2011). On the other hand, the REN gen presents two relevant SNPs, one in the intron 4 [G5795T (rs5707)] and one in the exon 2 [C4280A (rs5705)].…”
Section: Introductionmentioning
confidence: 97%
“…The T-allele of rs3789679 was found to be significantly associated with the increased risk of atherosclerosis and obesity involved with hypertension among the Saudi population. 58 The haplotype rs5051A, rs3789679C, rs2004776A, rs4762C, rs3789670G, rs2493132G, rs2478523C, rs7079C was found to be associated with the risk of myocardial infarction among the Europeans. 118 Our present study among both Hani and Yi populations showed no association of these two polymorphisms with EH.…”
Section: Discussionmentioning
confidence: 99%